1997
DOI: 10.1086/304392
|View full text |Cite
|
Sign up to set email alerts
|

Activity‐Related Radial Velocity Variation in Cool Stars

Abstract: Planets have been detected orbiting several solar-type stars using high-precision radial velocity (v r) measurements. While changes in v r can be measured with an accuracy of a few m s ?1 , there has been relatively little study of how other astrophysical processes, such as magnetic activity, may e ect the observed velocities. In this paper, we use published data and simple models to explore the contributions to v r from two activity-related sources, starspots and convective inhomogeneities, as these features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
473
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 468 publications
(498 citation statements)
references
References 50 publications
22
473
1
2
Order By: Relevance
“…It is also known that stellar activity can produce signals that can mimic planetary companions at different timescales (e.g. Saar & Donahue 1997;Queloz et al 2000;Santos et al 2010;Dumusque et al 2012;Kane et al 2016), even for stars with a low activity level (e.g. Santos et al 2014).…”
Section: Radial-velocity Fittingmentioning
confidence: 99%
“…It is also known that stellar activity can produce signals that can mimic planetary companions at different timescales (e.g. Saar & Donahue 1997;Queloz et al 2000;Santos et al 2010;Dumusque et al 2012;Kane et al 2016), even for stars with a low activity level (e.g. Santos et al 2014).…”
Section: Radial-velocity Fittingmentioning
confidence: 99%
“…Observationally, these inhomogeneities translate into flux variations, as well as into changes of both the shape and the centroid of spectral lines (Saar & Donahue 1997;Queloz et al 2001). Spots also typically impact spectral indices, whether designed to probe the chromosphere (to which photospheric spots have strong magnetic connections) or the photosphere (because spots have cooler spectra).…”
Section: Activity Analysismentioning
confidence: 99%
“…As demonstrated by Saar & Donahue (1997), the bisector analysis loses much of its diagnostic power when applied to slow rotators. In simulations of the impact of star spots on radialvelocity and bisector measurements, they found that, for a given spot configuration, the radial velocity varies linearly with v sin i, while the bissector span varies as (v sin i) 3.3 .…”
Section: Appendix A: Bisector Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Stellar activity can produce intrinsic RV variability and adds an additional noise source into the RV measurement (e.g. Saar & Donahue 1997). It can even mimic the RV signature of a short-period planet like in the case of HD 166435 (Queloz et al 2001).…”
Section: The Target Samplementioning
confidence: 99%